IoT-based Eyes Closure Alert System for Drowsy Driver - Nursyuhada Amir Shariffuddin; Ling, Yeong Tyng (Trends in Undergraduate Research, 2023)
Internet of Things (IoTs) is a technology that links objects and mechanisms to the Internet. IoT devices are deployed in a number of areas within the transportation sector, notably in security and surveillance. The ability to track driving behaviour on the road using IoT can improve driver safety and reduce traffic accidents. In this paper, a prototype system to detect a driver’s drowsiness is proposed. In particular, a facial landmark is used to extract the eye region, the eye aspect ratio, and closure patterns. This system will audibly alert the driver and invoke third party notification if drowsiness of the driver is detected. Through this system, traffic accidents caused by drowsy drivers can be avoided and driving behaviour can be evaluated by relevant personnel or employers.